Surgical principles for optimal treatment of esophagogastric junction adenocarcinoma. Issue 4 (11th June 2019) - Nobel, Tamar; Molena, Daniela
Abstract: The incidence of esophagogastric junction (EGJ) adenocarcinoma is increasing worldwide. Management of these tumors remains controversial given their unique location between the esophagus and the stomach. Debate surrounding the optimal therapy for EGJ adenocarcinoma has often centered around the tumor origin as defined by the Siewert classification system. However, the optimal surgical management should focus on adhering to important surgical principles that will allow for the best outcomes and prognosis regardless of tumor location including resection with appropriate and negative histological margins, adequate lymphadenectomy, minimization of morbidity and mortality, and preservation of quality‐of‐life. In this article, we provide a discussion of the controversy surrounding EGJ adenocarcinoma within the framework of these concepts.